Feasibility of implementing Extubation Advisor, a clinical decision support tool to improve extubation decision-making in the ICU: a mixed-methods observational study - Tim Ramsay; Andrew JE Seely; Karen EA Burns; Aimee J Sarti; Katina Zheng; Stephanie Sutherland; Rebecca Porteous; Irene Watpool; Christophe L Herry; Michael Hickey; Nathan B Scales; Caitlin Anstee; et al. (BMJ Open)
Objectives Although spontaneous breathing trials (SBTs) are standard of care to extubation readiness, no tool exists that optimises prediction and standardises assessment. In this study, we evaluated the feasibility and clinical impressions of Extubation Advisor (EA), a comprehensive clinical extubation decision support (CDS) tool.Design Phase I mixed-methods observational study.Setting Two Canadian intensive care units (ICUs).Participants We included patients on mechanical ventilation for ≥24 hours and clinicians (respiratory therapists and intensivists) responsible for extubation decisions.Interventions Components included a predictive model assessment, feasibility evaluation, questionnaires and interviews with clinicians.Results We enrolled 117 patients, totalling 151 SBTs and 80 extubations. The incidence of extubation failure was 11% in low-risk patients and 21% in high-risk patients stratified by the predictive model; 38% failed extubation when both the model and clinical impression were at high risk. The tool was well rated: 94% and 75% rated the data entry and EA report as average or better, respectively. Interviews (n=15) revealed favourable impressions regarding its user interface and functionality, but unexpectedly, also concerns regarding EA’s potential impact on respiratory therapists’ job security.Conclusions EA implementation was feasible, and users perceived it to have potential to support extubation decision-making. This study helps to understand bedside implementation of CDS tools in a multidisciplinary ICU.Trial registration number NCT02988167.